Bridging Health Information Access for Low-Income Parents of Children with Disabilities - Kurniawan, Reza (UPT Publikasi Ilmiah UNISBA, 2025)
This study explores self-education in health information seeking among parents of children with disabilities from low-income backgrounds. These parents face intersecting emotional, social, and financial burdens due to limited access to formal support and health resources. Using a qualitative method and in-depth interviews, the research examines how they navigate health information needs and educate themselves about their children’s conditions. Findings reveal a heavy reliance on informal sources—family, friends, and community members—which often leads to a mix of accurate advice and misinformation. Cultural beliefs also shape their understanding of disability, affecting their trust in and willingness to seek professional healthcare. Despite these constraints, self-education emerges as a critical tool for empowerment, enabling parents to make informed decisions and advocate for their children’s wellbeing. The study recommends designing targeted, culturally sensitive educational programs that address the specific health literacy gaps within this demographic. Community-based interventions and accessible, trustworthy digital content are essential to support informed choices. Theoretically, this study expands existing health information-seeking models by incorporating perspectives on socio-cultural mediation and digital inequity. It emphasizes the need to consider how localized belief systems and informal networks influence decision-making in marginalized populations navigating disability and healthcare challenges.